An empirical review of public policies on the sector of SMEs in the European Union - Grigorescu, Adriana; Ion, Amalia-Elena (Zielona Góra: Faculty of Economics and Management Press)
The paper aims to provide with a close picture of the SME public policies in one of the most prominent capitalist economies of the world, that of the European Union. In order to do this, a qualitative analysis has been undergone, on the basis of the following indicators: access to financial resources for SMEs, regulatory and legal frameworks for SMEs, and public assistance on information and knowledge about markets.
Keywords: public policy; qualitative analysis; content analysis; SME public policy; polityka publiczna; analiza jakościowa; analiza treści; polityka publiczna MŚP; małe i średnie przedsiębiorstwa